Canva Model Marketing Design Service with Muhammadiyah Young Farmers - Ade Eviyanti; M. Abror; Saiful Arifin (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article presents a community engagement initiative aimed at providing training and guidance to 20 young Muhammadiyah farmers on developing graphic design skills for agricultural marketing using the Canva application. The method employed involved Canva training, marketing material creation, result evaluation, and dissemination. Participants enthusiastically created diverse marketing graphics, including brochures, banners, posters, and product packaging. Evaluations and constructive feedback were provided to improve their work. The results of this initiative were disseminated through social media articles and scientific journals, alongside a small seminar to announce the outcomes. The Canva marketing model implementation empowered the young farmers, enabling them to effectively promote their agricultural products, boost sales, and enhance their overall livelihoods. Highlights: Training in Canva application: Equipping young Muhammadiyah farmers with graphic design skills to enhance marketing efforts for their agricultural products. Dissemination through multiple channels: Utilizing social media, scientific journals, and seminars to share the results of the Canva marketing model and its impact on young farmers. Empowering agricultural livelihoods: The initiative's focus on improving product promotion and sales contributes to the socio-economic well-being of young Muhammadiyah farmers. Keywords: Canva, marketing, Muhammadiyah, young farmers, agricultural products